Axilläre und perimamilläre Fox-Fordyce-Erkrankung (apokrine Miliaria) bei einer 19-jährigen Patientin - Hanner, Susanne; Schneiderbauer, Roland; Enk, Alexander; Toberer, Ferdinand (Der Hautarzt, 2018)
Fox-Fordyce disease (FFD), also known as apocrine miliaria, is a rare and chronic skin disease characterized by itching and skin-colored, light brown or yellowish papules. FFD typically affects postpubertal young women between 13 and 35 years. The etiology is not completely known, but a hormonal component is in discussion. Furthermore, exacerbating factors like laser hair removal and hyperhidrosis have been described. Treatment of FFD is quite challenging, as the reported modalities mostly show limited success.
Online: 06 November 2017
Gesehen am 26.08.2019